Amycenone reduces excess body weight and attenuates hyperlipidaemia by inhibiting lipogenesis and promoting lipolysis and fatty acid β-oxidation in KK-Ay obese diabetic mice. (11th July 2022) - Kudo, Maya; Hayashi, Misa; Sun, Boju; Wu, Lili; Liu, Tonghua; Gao, Ming
Abstract: Excess body weight and hyperlipidaemia cause severe health problems and have social implications. Amycenone is an active substance extracted from Yamabushitake mushrooms with no reports of its activity against excess body weight and hyperlipidaemia. This research clarifies the effects and mechanisms of action of amycenone on the inhibition of body weight excess and hyperlipidaemia attenuation using KK- A y mice. Amycenone or water was administered to 8-week-old male KK- A y mice by gavage for 8 weeks. Their body weight and food intake were recorded during the experiment. At the end of the experimental period, the mice were dissected, and blood samples, lipid metabolism-related organs and tissues were collected and stored for further analysis. Amycenone treatment suppressed body weight gain and improved serum levels of fasting blood glucose and non-esterified fatty acids. Additionally, serum and hepatic cholesterol and triacylglycerol levels were reduced after this treatment, whereas the phosphorylation levels of AMPK, PKA and HSL increased and the expression level of FAS decreased. The protein level of C/EBPβ and gene expression level of Cpt1 were higher in the perirenal adipose tissue of amycenone-treated KK- A y mice. Furthermore, amycenone phosphorylated AMPK, PKA and ACC, and PPARγ expression was lower in the mesenteric adipose tissue. The phosphorylation levels of AMPK, LKB1, PKA and ACC were also induced, and FAS expression level was reduced in the liver of the amycenone-treated group. Amycenone could reduce excess body weight and attenuate hyperlipidaemia in KK- A y mice by inhibiting lipogenesis and promoting lipolysis through lipid metabolism pathway stimulation and fatty acid β-oxidation acceleration.